From teaching strategies to school systems: enhancing higher-order questioning skills in islamic religious education - Asmuki Asmuki; M. Holil; Djuwairiyah Djuwairiyah; Wardani Wardani; Mohamad Aso Samsudin (Institute of Computer Science (IOCS), 2026)
Islamic Religious Education (IRE) in secondary schools is often implemented in a normative and text-oriented manner, limiting dialogical learning and the development of students’ questioning skills. Existing studies largely view questioning skills as outcomes of individual teachers’ pedagogical practices, paying little attention to school-level managerial factors. Addressing this gap, this qualitative descriptive study examines students’ questioning skills in IRE and the pedagogical and managerial factors supporting their development at SMP Negeri 1 Asembagus. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using the Miles and Huberman interactive model with triangulation. The findings show that students’ questioning skills developed from LOTS to HOTS levels. Importantly, this development is supported not only by interactive pedagogy but also by instructional leadership, continuous academic supervision, curriculum guidance, and a sustainable evaluation culture, indicating a synergistic interaction between pedagogy and school management. The synergistic findings of teacher and managerial pedagogy of teachers and principals are the theoretical contribution of this research, which practically has implications for the need for visionary, progressive, and innovative school principals to improve teacher pedagogics that can improve the quality of the learning process.